Application of cluster analysis to the study of spatial patterns of earthquakes in Azerbaijan and adjacent territories - Skurativskyi, S.I.; Mykulyak, S.V.; Semenova, Yu.V.; Skurativska, K.S. (Geofizicheskiy Zhurnal, 2025)
Based on the data of the earthquake catalog in Azerbaijan and adjacent areas from 2010 to 2023, a procedure for dividing earthquakes into clusters was developed using the DBSCAN algorithm for Python. In the process of dividing into clusters, a number of indicators were used that allowed optimizing the number of clusters and the number of earthquakes in the clusters. A comparison of the location of earthquake clusters with tectonic faults in this region demonstrated their high correlation.